Comparison of the effects of communication and conflict resolution skills training on mental health. - Askari, Mahin; Mohd Noah, Sidek; Hassan, Siti Aishah; Baba, Maznah (Canadian Center of Science and Education, 2013)
This study examined the effects of communication and conflict resolution skills training on mental health among Iranian couples based on the PREPARE/ENRICH program. In this study, mental health was measured by General Health Questionnaires (GHQ28). The study adopted a pre-and post-control group design in emphasizing the effects of communication training and conflict resolution skills on mental health. The participants in this research consisted of couples who were referred to the researcher by counseling center. The referrals were done for about two months in 2009. Their problems included marital problems and marital conflicts, commonly categorized as marital dissatisfaction, which were identified after a formal interview, testing and screening. In order to assign the experimental and control groups, purposive random sampling was employed. One hundred and eight participants comprised of 54 married couples were divided equally between control and experimental groups and the training sessions lasted for eight weeks. In this training program, researchers focused on the dependent variable of mental health, while communication and conflict resolution skills training were the independent variables. Specifically, the t-test statistical analysis was employed to test for the potential significant differences in couples’ scores of mental health between (i) the pre-and post-training scores for couples of the experimental group; and (ii) between the post-training scores for the couples of the two groups. The results indicated that teaching communication and conflict resolution skills had significant positive effects on the mental health scores obtained from the studied couples.